2017
DOI: 10.1021/acs.orglett.7b00418
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of (−)-Acetylapoaranotin

Abstract: The first enantioselective total synthesis of the epipolythiodiketopiperazine (ETP) natural product (−)-acetylapoaranotin (3) is reported. The concise synthesis was enabled by an eight-step synthesis of a key cyclohexadienol-containing amino ester building block. The absolute stereochemistry of both amino ester building blocks used in the synthesis is set through catalytic asymmetric (1,3)-dipolar cycloaddition reactions. The formal syntheses of (−)-emethallicin E and (−)-haemotocin are also achieved through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…Simultaneously, Reisman’s group also reported the total synthesis of (−)-Acetylapoaranotin using a very close methodology [ 196 ]. Owing to the nonsymmetric nature of this compound, the procedure had to be a step-wise preparation of two proline key intermediates which were readily coupled and finally sulfenylated.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Simultaneously, Reisman’s group also reported the total synthesis of (−)-Acetylapoaranotin using a very close methodology [ 196 ]. Owing to the nonsymmetric nature of this compound, the procedure had to be a step-wise preparation of two proline key intermediates which were readily coupled and finally sulfenylated.…”
Section: Alkaloidsmentioning
confidence: 99%
“…[7] Reisman and co-workers furtherp ursuedt heir synthetic efforts towardD TPs and disclosed the synthesis of the challenging heterodimeric 7-5-6-5-6 DTP (À)-acetylapoaranotin (5). [8] Noteworthy,t he strategies used in these DTP total syntheses are comparable, with the initial construction of the AB/DE bicyclic systems and the latestage assembly of the central DKP ring C. In addition to these successfully completed total syntheses, as ignificant number of synthetic studies toward other DTPs were also reported. [9] Amongt hem, unfruitful attempts from the Carreira, Diver, Metz and He groups to access the scabrosin esters, [10] such as scabrosin diacetate 6,a ne poxide-containing DTP with nanomolar in vitro activity against human breast MCF7 cancer cells, [11] highlight the challenges of total synthesis of natural products from this family.…”
Section: Introductionmentioning
confidence: 96%
“…This 'oxidase phase' would be followed by the late-stage introductiono ft he sulfur atoms at C2/C2' in either dithioether or epidisulfide form, depending on the targeted DTP.E arlier studies already reportedt he sulfenylation of analogous DKP systems, [18,19] however this transformation was only rarely describedo nh eavily functionalized substrates. [2,[5][6][7][8] The commoni ntermediate 16,k eystone of this divergent total synthesis, would be formed via at wofold application of our C(sp 3 )ÀHa lkenylation methodology,h ence forging the C3-C4 and C3'-C4'b onds in as ingle transformation from the divinyl triflate 17.T his double C(sp 3 )ÀHa ctivation reactionw ould be crucial to the success of the synthesis, and therefore would need to be efficient, high-yielding and easily scalable to allow substantial amounts of 16 to be quickly obtained, in order to explore differentr outes toward the DTP targets. Precedents for this type of intramolecular C(sp 3 )ÀHa lkenylation of cyclohexenyl bromides [20] and triflates [21] had been reported, but this transformation featuring ad ouble C(sp 3 )ÀHa ctivation is unprecedented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such sensitizer-free photocatalytic reactions have generally been designed based on electron donor-acceptor complexes that have absorption maxima at relatively longer wavelengths. [6] Furthermore, Melchiorre, [7] Glorius, [8] Hong, [9] Cho, [10] and Wang [11] have recently achieved this class of transformation without reliance on these complexes.…”
Section: Introductionmentioning
confidence: 99%